EDUCATIONAL POLICY REFORMS IN ELEMENTARY EDUCATION IN TWO MERCOSUR COUNTRIES: BRAZIL AND ARGENTINA - Paz Brittes Panke, Viviane (Revista Gênero e Interdisciplinaridade, 2023)
This study aims to identify and describe a specific educational process that has been common in its general structure in at least two countries in the Mercosur region, in which the following countries were listed for analysis: Brazil and Argentina. Where a descriptive comparison will be made of its laws regulating education. In addition to the specific aspects that mark the particularity of each of these countries, there is also the parallel historical evolution, where the main milestones in terms of educational policy occurred almost at the same time in all of them. The educational policies in the countries that correspond to the MERCOSUR region, specifically Uruguay, Brazil, Argentina and Chile, the latter as an Associated State, that is, one of the countries that signed free trade agreements with MERCOSUR in order to boost their economies and commercial exchanges, but which do not have the same advantages as associate members.